Culture and power in cultural studies : the politics of signification - Storey, John, 1950- (Edinburgh University Press, 2010)
Culture and Power in Cultural Studies is a collection of John Storey's best and most significant contributions to the field of cultural studies, spanning 25 years. Covering a variety of topics, all chapters share a common focus on culture and power and the politics of signification: the struggle to define social reality; to give the world and its contents meaning in particular ways to generate desired effects of power. Chapters are informed by history and organised by theory, and have been revised and rewritten to create an engaging volume. Twelve chapters expand and elaborate certain key ideas.